Consent process for US-based family reference DNA samples. (January 2018) - Katsanis, Sara H.; Snyder, Lindsey; Arnholt, Kelly; Mundorff, Amy Z.
Highlights: Family reference samples (FRS) are essential for missing persons' investigations. Informed consent practices for FRS collection are variable. FRS consent should cover risks and benefits of and protections for participation. Standardization of FRS consent will improve protocols in DVI and missing persons' investigations. Abstract: DNA collection from family members of the missing is a tenet for missing persons' and mass fatality investigations. Procedures for consenting family members are disparate, depending on the context supporting the reason for sample collection. While guidelines and best practices have been developed for handling mass fatalities and for identification of the missing, these guidelines do not address standard consent practices for living family members of potential victims. We examined the relevant U.S. laws, international guidelines and best practices, sampled consent forms currently used for DNA collection of family members, and drafted model language for a consent form to communicate the required and recommended information. We modeled the consent form on biobank consenting practices and tested the consent language among students and the general population for constructive feedback and readability. We also asked respondents to consider the options for DNA collection and either hypothetically agree or disagree. The model language presented here highlights information important to relay in consent processes and can serve as a foundation for future consent practices in mass fatalities and missing persons' investigations.